Effect of optimal Multi-DG siting and sizing in transmission system using hybrid optimization technique for voltage control - Sharifah A. Shaaya; Ismail Musirin; Shahril I. Sulaiman; Mohd H. Mansor; Sharifah A. S.Mustaffa (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The advancement of Distributed Generation (DG) technologies have caused great impact to power system operation. Inappropriate installation of DGs may lead to over-compensation or under-compensation situation. Thus, a reliable optimization is urgent to avoid any unwanted effect. This paper analyses the installation impact of different types-multi-DGs determined using a pre-developed hybrid optimization technique termed as Immunized-Brainstorm-Evolutionary Programming (IBSEP). It is imperative to study the effect of multi-DGs installation such that a relevant utility can make a correct decision, whether its installation is worth or vice versa. Rigorous study has been conducted in terms of identifying the optimal location and sizing, installed on transmission system for voltage control involving different DG types. Comprehensive results are embedded in this paper to demonstrate the effect of multi-DGs installation in transmission system which in turns beneficial to the utility.